1992
DOI: 10.1139/y92-271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated potassium on the ion content of mouse astrocytes and neurons

Abstract: Potassium is tightly regulated within the extracellular compartment of the brain. Nonetheless, it can increase 3- to 4-fold during periods of intense seizure activity and 10- to 20-fold under certain pathological conditions such as spreading depression. Within the central nervous system, neurons and astrocytes are both affected by shifts in the extracellular concentration of potassium. Elevated potassium can lead to a redistribution of other ions (e.g., calcium, sodium, chloride, hydrogen, etc.) within the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
(17 reference statements)
3
14
1
Order By: Relevance
“…We reported hypokalemia with unaltered Mg 2+ and Ca 2+ levels in untreated epileptics (P<0.01) (Tables 2 and 4) which agrees with many studies (42,58,61,62). While we found no difference in the serum K + levels in different treated groups (Tables 2 and 4), White et al (58) reported elevation of K + levels during periods of intense seizure activity.…”
Section: +supporting
confidence: 90%
See 2 more Smart Citations
“…We reported hypokalemia with unaltered Mg 2+ and Ca 2+ levels in untreated epileptics (P<0.01) (Tables 2 and 4) which agrees with many studies (42,58,61,62). While we found no difference in the serum K + levels in different treated groups (Tables 2 and 4), White et al (58) reported elevation of K + levels during periods of intense seizure activity.…”
Section: +supporting
confidence: 90%
“…While we found no difference in the serum K + levels in different treated groups (Tables 2 and 4), White et al (58) reported elevation of K + levels during periods of intense seizure activity. Generally, the deficiency in K + is correlated to hypomagnesaemia and hypocalcaemia (42).…”
Section: +contrasting
confidence: 75%
See 1 more Smart Citation
“…Decreased glucose uptake and hypometabolism have been observed in seizure foci (Janigro, 1999). Also, astrocytes and endothelial cells play important roles in regulating intercellular levels of potassium and other ions that are important in brain electrophysiology (MacVicar, 1989;O'Donnell et al, 1995;Walz, 2000;White et al, 1992). Lost functions of astrocytes have also been linked to epileptic seizure (Heinemann et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The furosemidesensitive cotransport system appears to require some what higher concentrations of K + for maximum stimula tion than the ouabain-sensitive N a+/K + exchange but the exact correlation between the extracellular K + concentra tion and the activity of this system is disputed, since Walz and Hertz [42] and Chen et al [40] report maxi mum activity al higher [K+]0 concentrations than Walz and Hinks [36], A possible explanation for this discrep ancy might be that the latter authors compensated for the increase in K+ in the incubation medium by a corre sponding decrease in Na+ which may have become ratelimiting for the uptake. Jameson et al [61J concur in the conclusion that oxidative metabolism in astrocytes can be considerably increased above its resting level, in their studies by uncoupling with dinitrophenol [61], but they did not report any effects of exposure to excess K+.A moderate increase in the extracellular K+ concen tration beyond its resting level does not stimulate Na+,K+-ATPase activity in neurons obtained by gradient centrifugation [59], and there is no elevation in intracel lular K + concentration in cerebral cortical cultures highly enriched in GABAergic neurons when the extracellular K+ concentration is raised from 5 to 10 mM [53]. In the glutamatergic cerebellar granule cell neurons, the rate of both glucose ( fig.…”
mentioning
confidence: 99%